PERTANGGUNGJAWABAN RUMAH SAKIT DAN DOKTER MENOLAK PASIEN KURANG MAMPU BERDASARKAN UU NO 36 TAHUN 2009 - Brata Yudha Purba; Felix Michael Martua Sitorus; Sonya Airini Batubara (Sekolah Tinggi Ilmu Hukum Awang Long, 2021)
Health is the right of all human beings, which means that everyone has the same right to obtain health services whose health quality is safe and affordable. One of the developments in the health sector has a great degree of development in the development of human resources because everyone has the right to obtain medical services, even those who are less fortunate. In a bad service doctors and hospitals or said to be a denial of medical services to patients in need is often called malpractice. Countermeasures against refusal to provide medical service actions in order to tighten the imposition of sanctions on doctors and hospitals based on Law Number 36 of 2014 concerning Health Workers. The hospital leadership is responsible if there is a violation that is in accordance with the law No. 36 of 2009 concerning health. In addition to criminal liability, civil liability can also be needed because the injured party can obtain compensation in the form of compensation from hospitals that do not provide hospital services that result in losses for others.